2018
DOI: 10.1093/ofid/ofy210.559
|View full text |Cite
|
Sign up to set email alerts
|

551. MK-8591 Does Not Alter the Pharmacokinetics of the Oral Contraceptives Ethinyl Estradiol and Levonorgestrel

Abstract: BackgroundOver 2 million girls and young women are living with HIV, being newly infected at disproportionately high rates. HIV infection adds risks to pregnancy, including vertical transmission and maternal death. Hormonal contraceptives are among the most effective reversible contraceptives, but they have clinically meaningful drug–drug interactions (DDI) with many antiretrovirals (ARV). MK-8591 is a novel nucleoside reverse transcriptase translocation inhibitor (NRTTI) currently in Phase 2 clinical developme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Another PK and safety study demonstrated no meaningful drug–drug interactions between islatravir and tenofovir disoproxil fumarate, which is eliminated renally via OAT1 and OAT3, and dolutegravir, which is hepatically metabolized by UGT enzymes and CYP3A4 [ 70 , 71 , 76 ]. No significant drug–drug interactions have been observed following co-administration of islatravir with levonorgestrel/ethinyl estradiol [ 77 ], common components of hormonal contraceptives that are extensively metabolized by CYP3A4, are glucuronidated, and undergo biliary and urinary excretion [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Another PK and safety study demonstrated no meaningful drug–drug interactions between islatravir and tenofovir disoproxil fumarate, which is eliminated renally via OAT1 and OAT3, and dolutegravir, which is hepatically metabolized by UGT enzymes and CYP3A4 [ 70 , 71 , 76 ]. No significant drug–drug interactions have been observed following co-administration of islatravir with levonorgestrel/ethinyl estradiol [ 77 ], common components of hormonal contraceptives that are extensively metabolized by CYP3A4, are glucuronidated, and undergo biliary and urinary excretion [ 78 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding is of particular clinical relevance for PLWH who may require polypharmacy for the management of both HIV and common comorbidities, such as diabetes, cardiovascular disease, and depression. Islatravir is not expected to interact with the major pathways associated with other antiretroviral agents, including dolutegravir, doravirine, and tenofovir disoproxil fumarate [ 54 , 71 , 76 ] as well as with commonly prescribed medications, including metformin, omeprazole, clopidogrel, statins, alprazolam, buprenorphine/naloxone, selective serotonin reuptake inhibitors, oral contraceptives, and rifampin [ 77 ]. These results support the continued clinical evaluation of islatravir as an option across diverse populations for the treatment and prevention of HIV-1 infection.…”
Section: Discussionmentioning
confidence: 99%
“…10 Adenosine deaminase is the only known contributor to islatravir metabolism, 11 and islatravir is not expected to have significant drug-drug interactions. [12][13][14] In addition, food had little impact on islatravir PK. 10 The long intracellular half-life and high potency of ISL-TP allow for a variety of islatravir dosing options, ranging from once daily (QD) to less frequent dosing schedules.…”
Section: Introductionmentioning
confidence: 99%
“…29 Furthermore, no significant drug-drug interactions have been observed following coadministration of islatravir with levonorgestrel and/or ethinyl estradiol, common components of hormonal contraceptives. 35 A potential limitation of this trial is that only a single dose of islatravir was administered during each treatment period. However, given what is known about islatravir, dolutegravir, and tenofovir, islatravir is not anticipated to affect the pharmacokinetics of either drug regardless of dose or number of doses.…”
Section: Discussionmentioning
confidence: 99%
“… 29 Furthermore, no significant drug‐drug interactions have been observed following coadministration of islatravir with levonorgestrel and/or ethinyl estradiol, common components of hormonal contraceptives. 35 …”
Section: Discussionmentioning
confidence: 99%